High-Efficiency Polymer LEDs with Fast Response Times Fabricated via Selection of Electron-Injecting Conjugated Polyelectrolyte Backbone Structure. - Suh,M; Bailey,J; Kim,SW; Kim,K; Yun,DJ; Jung,Y; Hamilton,I; Chander,N; Wang,X; Bradley,DD; Jeon,DY; Kim,JS (ACS Applied Materials & Interfaces, 2015)
Imidazolium ionic side-group-containing fluorene-based conjugated polyelectrolytes (CPEs) with different π-conjugated structures, poly[(9,9-bis(8'-(3″-methyl-1″-imidazolium)octyl)-2,7-fluorene)-alt-2,7-(9,9-dioctylfluorene)] dibromide (F8im-Br) and poly[(9,9-bis(8'-(3″-methyl-1″-imidazolium)octyl)-2,7-fluorene)-alt-(benzo(2,1,3)thiadiazol-4,8-diyl) dibromide (F8imBT-Br), are synthesized and utilized as an electron injection layer (EIL) in green-emitting F8BT polymer light-emitting diodes (PLEDs). Both CPE EIL devices significantly outperform Ca cathode devices; 17.9 cd A(-1) (at 3.8 V) and 16.6 lm W(-1) (at 3.0 V) for F8imBT-Br devices, 11.1 cd A(-1) (at 4.2 V) and 9.1 lm W(-1) (at 3.4 V) for F8im-Br devices, and 7.2 cd A(-1) (at 3.6 V) and 7.0 lm W(-1) (at 3.0 V) for Ca devices. Importantly, unlike the F8im-Br EIL devices, F8imBT-Br PLEDs exhibit much faster electroluminescence turn-on times (<10 μs) despite both EILs possessing the same tethered imidazolium and mobile bromide ions. The F8imBT-Br devices represent, to the best of our knowledge, the highest efficiency in thin (70 nm) single-layer F8BT PLEDs in conventional device architecture with the fastest EL response time using CPE EIL with mobile ions. Our results clearly indicate the importance of an additional factor of EIL materials, specifically the conjugated backbone structure, to determine the device efficiency and response times.